Results from a cervical cancer screening program in Samsun, Turkey - Hatice Nilden Arslan; Muhammet Ali Oruc (BMC, 2022)
Abstract Background Cervical cancer is a preventable disease. This study aimed to share the results of the national cervical cancer screening program performed in primary health care institutions in Samsun between 2015 and 2019. Methods Women aged 30-65 years who were screened for cervical cancer in screening centers of Samsun between January 01, 2015, and December 31, 2019, were included in this descriptive study. The data were obtained from the automation program of the "National Human Papilloma Virus (HPV) Laboratory Application" used by the Provincial Directorate of Health Cancer Unit through filtering the completion time of the tests, and all results were evaluated without sampling. Thus, data were presented using descriptive statistics. Results The mean age of 89,302 women included in the cervical cancer screening program was 45.9 ± 9.0 years. Of the samples obtained from the participants, 1.0% were determined as insufficient material, 94.1% as HPV-negative, and 4.9% as HPV-positive. The most common HPV genotypes were 16, 51, 31, and 52. Of the 4337 HPV-positive women, 74.7% of the pap smear results were negative (including infection, 36.5%), and the most common premalignant lesions were atypical squamous cells of undetermined significance in 7.1% and low-grade squamous intraepithelial lesions in 6.9%. HPV 16/18 was also observed in 31.7% of HPV-positive women. Seven hundred ninety-five women were referred to a specialist physician for further examination and treatment within the scope of the screening algorithm. Conclusion Detecting HPV-positivity by reaching more women within the national cervical cancer screening program's scope is vital in fighting against this disease. The effectiveness of cancer screening programs should be increased by ensuring community participation through awareness activities.